Effect of intravitreal anti-vascular endothelial growth factor therapy on the risk of arterial thromboembolic events: a meta-analysis. - Jin-Wei Cheng (Public Library of Science (PLoS), 2012)
Background Intravitreal anti-vascular endothelial growth factor (VEGF) monoclonal antibodies are used in ocular neovascular diseases. A consensus has emerged that intravenous anti-VEGF can increase the risk of arterial thromboembolic events. However, the role of intravitreal anti-VEGF in arterial thromboembolism is controversial. Therefore, we did a systematic review and meta-analysis to investigate the effects of intravitreal anti-VEGF on the risk of arterial thromboembolic events. Methods Electronic databases were searched to identify relevant randomized clinical trials comparing intravitreal anti-VEGF with controls. Criteria for inclusion in our meta-analysis included a study duration of no less than 12 months, the use of a randomized control group not receiving any intravitreal active agent, and the availability of outcome data for arterial thromboembolic events, myocardial infarction, cerebrovascular accidents, and vascular death. The risk ratios and 95% CIs were calculated using a fixed-effects or random-effects model, depending on the heterogeneity of the included studies. Results A total of 4942 patients with a variety of ocular neovascular diseases from 13 randomized controlled trials were identified and included for analysis. There was no significant difference between intravitreal anti-VEGF and control in the risk of all events, with risk ratios of 0.87 (95% CI, 0.64 to 1.19) for arterial thromboembolic events, 0.96 (95% CI, 0.55-1.68) for cerebrovascular accidents, 0.69 (95% CI 0.40-1.21) for myocardial infarctions, and 0.68 (95% CI, 0.37-1.27) for vascular death. Conclusions The strength evidence suggests that the intravitreal use of anti-VEGF antibodies is not associated with an increased risk of arterial thromboembolic events.